Green Sukuk sebagai Instrumen Hukum Ekonomi Syariah untuk Pembangunan Berkelanjutan di Indonesia - Damar Tangguh Rabani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This paper explores the role of Green Sukuk in advancing sustainable development in Indonesia, with a focus on its alignment with Islamic law and the principles of maqashid al-shariah. The research aims to examine the impact of Green Sukuk as a financial instrument in supporting environmentally friendly projects such as renewable energy, waste management, and green transportation. Using a qualitative approach, the study analyzes the legal, economic, and ethical dimensions of Green Sukuk, as well as its contributions to social justice and environmental sustainability. The findings reveal that Green Sukuk not only fulfills Islamic financial principles by being free from haram elements like riba, gharar, and maisir, but also serves as an instrument for equitable development by directing funds to sustainable projects that benefit society and the environment. However, the study identifies challenges such as limited private sector involvement, lack of in-depth project evaluation, and insufficient public awareness. The research suggests that future studies should focus on evaluating the effectiveness of Green Sukuk projects on the ground, conduct international comparisons to identify best practices, and enhance the role of the private sector and public engagement in expanding the scope of Green Sukuk. Ultimately, this paper contributes to the growing discourse on Islamic finance and sustainability, demonstrating that Green Sukuk is not only a financial tool but also a medium for social and environmental responsibility in line with Islamic teachings.